187k views
5 votes
How do you get the answer to a math problem -k+h+kh k=-5 h=-2

2 Answers

0 votes

Answer:

7

Explanation:

you have to put the numbers in for the variables

-5+2+5(2)

User Odhran Roche
by
4.4k points
5 votes

Answer:

Final answer is 13.

Explanation:

Given expression is

-k+h+kh

We also have been given values of h and k as:

k=-5 h=-2

to simplify the given expression, we just need to plug the given values of k=-5 and h=-2 into -k+h+kh

-k+h+kh


=-(-5)+(-2)+(-5)(-2)


=5+(-2)+(-5)(-2)


=5-2+(-5)(-2)


=5-2+(10)


=5-2+10


=3+10


= 13

Hence final answer is 13.

User Dauren
by
4.7k points